The Influence of the Faculty of Sharia and Islamic Economics Information System (SIFASE) on Student Satisfaction at the FSEI Ibrahimy University Situbondo - Syamhadi; Nanda Hidayan Sono; Nadzirotul Fithriyah; Helyatin Nisyak; Muhammad Fauzen Adiman (Universitas Muhammadiyah Jember, 2026)
This study aims to analyze the effect of the Faculty of Sharia and Islamic Economics Information System (SIFASE) on student satisfaction at the Faculty of Sharia and Islamic Economics (FSEI), Ibrahimy University Situbondo. SIFASE was developed to support various academic services that were not fully accommodated by the Academic Information System (SIAKAD), including field practice management, community service programs, thesis submission, and graduation administration. This research employed a quantitative approach using accidental sampling techniques. The population consisted of 192 seventh-semester students, while 99 respondents were successfully analyzed. Data were collected through observation, questionnaires, and documentation. Data analysis was conducted using simple linear regression preceded by validity, reliability, normality, and linearity tests. The results indicate that SIFASE has a positive and significant effect on student satisfaction, with a t-value of 8.330 and a significance level of 0.000 < 0.05. Furthermore, the coefficient of determination (R²) value of 0.417 indicates that SIFASE explains 41.7% of the variation in student satisfaction, while the remaining 58.3% is influenced by other factors outside the research model. These findings demonstrate that SIFASE contributes to improving academic service quality and student satisfaction within FSEI Ibrahimy University Situbondo.